2014
DOI: 10.1016/j.compositesa.2014.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Strength prediction in CFRP woven laminate bolted single-lap joints under quasi-static loading using XFEM

Abstract: a b s t r a c tThis paper is concerned with modelling damage and fracture in woven fabric CFRP single-lap bolted joints that fail by net-tension. The approach is based on the assumption that damage (matrix cracking, delamination and fibre tow fracture) initiates and propagates from the hole in a self-similar fashion. A traction-separation law (based on physically meaningful material parameters) is implemented within an Extended Finite Element Method (XFEM) framework and used to predict the joint strength. Reas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 15 publications
2
20
0
Order By: Relevance
“…The local failure (bearing stress) initially occurred prior to ultimately net-tension failure. Similar findings were found by Ahmad et al [10] in woven fabric CFRP bolted joints at which intermediate W/d net-tension failure was preceded by local bearing damage with unclamped condition. They also suggested full bearing failures seen to be more pronounce in quasi-isotropic lay-ups compared to cross-ply lay-ups.…”
Section: Iconcees 2015supporting
confidence: 79%
“…The local failure (bearing stress) initially occurred prior to ultimately net-tension failure. Similar findings were found by Ahmad et al [10] in woven fabric CFRP bolted joints at which intermediate W/d net-tension failure was preceded by local bearing damage with unclamped condition. They also suggested full bearing failures seen to be more pronounce in quasi-isotropic lay-ups compared to cross-ply lay-ups.…”
Section: Iconcees 2015supporting
confidence: 79%
“…Most of these studies are focused on the stress/strain distribution around the fastened hole to predict the crack initiation stress. Ahmad et al [8,9] studied the effect of different seven carbon fiber reinforced polymer (CFRP) woven fabric lay-up configurations on ultimate strength of double-lap bolted joint. They concluded that, the different lay-ups give different stress distributions along the hole boundary angle h, see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, surface roughness due to the machining operation will increase the likelihood of a surface fatigue crack initiating and propagating under changing load conditions [7]. Recently, strength prediction of single-lap or double-lap joints failed by net-tension have been studied using different methods such as extended finite element [8,9], cohesive zone model [10][11][12], and coupling techniques between the acoustic emission and digital image [13]. Most of these studies are focused on the stress/strain distribution around the fastened hole to predict the crack initiation stress.…”
Section: Introductionmentioning
confidence: 99%
“…also on the notched strength of the laminate [57]. The joint efficiency of bolted connections made on CFRP/metals hybrid joints typically ranges between 45% -100% [58,59].…”
Section: Joint Efficiencymentioning
confidence: 99%